Mosaic Evolution of Membrane Transporters in Galdieriales - Claudia Ciniglia; Antonino Pollio; Elio Pozzuoli; Marzia Licata; Nunzia Nappi; Seth J. Davis; Manuela Iovinella (Plants, 2025)
Membrane transporters are vital for solute movement and localisation across cellular compartments, particularly in extremophilic organisms such as Galdieriales. These red algae thrive in geothermal and metal-rich environments, where adaptive transporter systems contribute to their metabolic flexibility. While inventories of transporter genes in the species Galdieria sulphuraria have previously been compiled, their phylogenetic origins remain incompletely resolved. Here, we conduct a comparative phylogenetic analysis of three transporter families—Major Facilitator Superfamily (MFS). Amino acid–Polyamine–Organocation (APC) and the natural resistance–associated macrophage protein (Nramp)—selected from overexpressed transcripts in G. sulphuraria strain SAG 107.79. Using sequences from six Galdieriales species and orthologs from diverse taxa, we reconstructed maximum likelihood trees to assess conservation and potential horizontal gene transfer (HGT). The MFS subfamilies revealed contrasting patterns: sugar porters (SPs) exhibited polyphyly and fungal affinity, suggesting multiple HGT events, while phosphate:H+ symporters (PHSs) formed a coherent monophyletic group. APC sequences were exclusive in G. sulphuraria and extremophilic prokaryotes, indicating a likely prokaryotic origin. In contrast, Nramp transporters were broadly conserved across eukaryotes and prokaryotes, showing no signs of recent HGT. Together, these findings highlight the mosaic evolutionary history of membrane transporters in Galdieriales, shaped by a combination of vertical inheritance and taxon-specific gene acquisition events, and provide new insight into the genomic strategies underpinning environmental resilience in red algae.